Pengaruh Kualitas Produk, Promosi Penjualan , Persepsi Harga Terhadap Kepercayaan Dan Dampaknya Pada Keputusan Pembelian Di Qonita Property Depok - Humam; Rahayu Lestari; Andini Nurwulandari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
benefits. Based on this concept, consumer knowledge is closely related to the discussion of attitudes because consumer knowledge is consumer trust. The purpose of this study was to determine the extent to which product quality, sales promotion, and price perception applied at Qonita Property affect trust informing purchasing decisions. The analytical method used is descriptive analysis to analyze the data in this study. In this study, there are 21 indicators, with a minimum sample of 105 respondents. The results of this study indicate that product quality, sales promotion, and price perception have a positive effect on trust and purchasing decisions at Qonita Property Depok.